Sevoflurane induces microRNA-18a to delay rat neurodevelopment via suppression of the RUNX1/Wnt/β-catenin axis - Jiang, Yuge; Liu, Yaobo; Sun, Yuhui; Liu, Yongzhe; Feng, Long; Duan, Mingda; Liu, Yi; Xu, Longhe (Cell death discovery, 2022)
Sevoflurane anesthesia is reported to repress neurogenesis of neural stem cells (NSCs), thereby affecting the brain development, but the underlying mechanism of sevoflurane on the proliferation of NSCs remains unclear. Thus, this study aims to discern the relationship between sevoflurane and NSC proliferation. Bioinformatics tools were employed to predict the expression of microRNA-18a (miR-18a) in 9-day-old neonatal rat hippocampal tissues after sevoflurane treatment and the downstream genes of miR-18a, followed by a series of assays to explore the relationship among miR-18a, runt related transcription factor 1 (RUNX1), and β-catenin in the hippocampal tissues. NSCs were isolated from the hippocampal tissues and subjected to gain-/loss-of-function assays to investigate the interactions among miR-18a, RUNX1, and β-catenin in NSCs and their roles in NSC development. Bioinformatics analysis and experimental results confirmed high expression of miR-18a in rat hippocampal tissues and NSCs after sevoflurane treatment. Next, we found that miR-18a downregulated RUNX1 expression, while RUNX1 promoted NSC proliferation by activating the Wnt/β-catenin signaling pathway. The behavioral experiments also showed that sevoflurane caused nerve injury in rats, whilst RUNX1 overexpression protected rat neurodevelopment. Our findings uncovered that sevoflurane attenuated NSC proliferation via the miR-18a-meidated RUNX1/Wnt/β-catenin pathway, thereby impairing rat neurodevelopment.